Context Effects on Spoken and Written Word Recognition - Sonja Kitanovska-Kimovska (Center for Promoting Ideas, 2015)
There has been a long-standing debate as to how the individual stages of language processing function and what their relational structure is. At one extreme are the widespread models of interactive activation allowing for higher level influences on lower level operations in the system. At the other are the proponents of the modular system of autonomous stages allowing only for unidirectional flow of information. In this paper I will argue for the position that context effects are the result of a top-down spread of activation. Discussing various studies on spoken and written word recognition, I show how context helps the word recognition process.
Keywords: context effects, spoken word recognition, written word recognition